A STUDY ON JOB SATISFACTION OF WOMEN CONSTABLES DURING COVID- 19 IN KANNIYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Pursuing job is the most difficult thing during the Covid-19 pandemics, whoseconsequences impair the capacities of workers at all organizational levels and imposeunexpected challenges on superiors.Nevertheless, the scientific literature still lacks onoverview of how researchers have been covering the issue. This article presents systematicreview to investigate the job satisfaction of Covid-19 on women constables and how theyadapt the situation to amid the pandemic in Kanniyakumari district. This study finds that lackof facilities, lack of rest, insecure work at night, inadequate income and increased job stress.